Nuts & bolts : a matter of fact guide to science fair projects - Van Deman, Barry A.; McDonald, Ed. (Harwood Heights, Ill. : Science Man Press, 1980)
Outlines ways to produce more scientific, more creative, and more presentable science fair projects.
"Science blueprint": 1 ill. inserted.
Includes index.
Bibliography: p. 59-60.
Keywords: Science -- Exhibitions -- Juvenile literature; Science -- Experiments -- Juvenile literature; Experiments; Science -- Exhibitions; Science -- Experiments